89Zirconium-labelled girentuximab (89Zr-TLX250) PET in Urothelial Cancer Patients (ZiPUP): protocol for a phase I trial of a novel staging modality for urothelial carcinoma. Issue 4 (15th April 2022) - Al-Zubaidi, Mohammed; Viswambaram, Pravin; McCombie, Steve; Liow, Elizabeth; Lenzo, Nat; Ferguson, Tom; Redfern, Andrew D; Gauci, Richard; Hayne, Dickon
Abstract : Introduction: Bladder cancer is a lethal disease with a rising incidence on a background of limited conventional imaging modalities for staging (either CT of the chest-abdomen-pelvis or 18F-fluorodeoxyglucose positron emitting tomography (FDG-PET/CT)). CT is known to have relatively low sensitivity for detecting low volume metastatic disease, an important goal when considering surgical interventions entailing significant potential morbidity. FDG is also limited, being predominantly renally excreted and, therefore, producing intense non-specific activity in the urinary tract, which limits its utility to detect bladder and upper tract lesions, or nodal metastases in close proximity to the urinary tract. 89 Zirconium-labelled girentuximab ( 89 Zr-TLX250) may have utility in the accurate staging of bladder and urothelial carcinomas, with less renal excretion as compared with FDG; however, this has not previously been investigated. Methods and analysis: 89 Zirconium-labelled girentuximab PET in Urothelial Cancer Patients is a single-arm phase I trial examining the feasibility of using 89 Zr-TLX250-PET/CT as a staging modality for urothelial and bladder carcinomas by examining isotope uptake by the cancer. This trial will also examine the safety and utility of 89 Zr-TLX250-PET/CT in patients either undergoing preoperative staging of bladder or other urothelial carcinomas for curative intent, or with known metastatic urothelial carcinomas. All participants will undergo 89 Zr-TLX250-PET/CT and will need to have undergone recent FDG-PET/CT for comparison. This trial aims to recruit 10 participants undergoing preoperative staging and 10 participants with known metastatic disease. The primary endpoint is feasibility defined by the ability to recruit to the target sample size within the study duration; secondary endpoints are safety, tolerability, sensitivity and specificity in detecting lymph node metastases compared with FDG-PET/CT. Ethics and dissemination: Ethics approval has been obtained from the South Metropolitan Health Service Human Research Ethics Committee (RGS0000003940). Eligible patients will only be enrolled after providing written informed consent. Patients will be given a full explanation, in lay terms, of the aims of the study and potential risks including as a written patient information sheet. Trial registration numbers: ACTRN12621000411842, NCT05046665 .